Distance education and distributed learning - Vrasidas, Charalambos; Glass, Gene V., 1940- (Emerald Publishing Limited : Information Age Publishing, 2002)
This work discusses issues relating to distance education and distributed learning. There are essays covering: rethinking assessment for the online environment; the role of collaborative learning in social and intellectual development; and the embodiment of knowledge in virtual environments.
Keywords: Distance education -- Computer-assisted instruction.; Educational technology.; Education -- Distance, Open & Online Education.; Open learning, distance education.; elektronické knihy; electronic books